Proceedings of Offshore Technology Conference 2009
DOI: 10.4043/otc-19787-ms
|View full text |Cite
|
Sign up to set email alerts
|

Oil Recovery and Surfactant Adsorption During CO2-Foam Flooding

Abstract: Three carbon dioxide (CO 2 ) foam flooding parameters are addressed in this paper: optimum gas fractional flow, surfactant adsorption behavior, and oil recovery versus CO 2 /aqueous phase injection methodologies. Experimental test conditions were selected to simulate some of the reservoirs in west Texas (1540 psig and 110°F). All tests in this study were conducted in fired Berea sandstone cores to minimize core property changes during a series of CO 2 foam flooding tests. CO 2 and aqueous phase were co-injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…(Bian et al, 2012;Chabert et al, 2014;Chang and Grigg, 1999;Dong, 2001; Kuehne et al, 1992;Moradi-Araghi et al, 1997;Mukherjee et al, 2014;Tsau and Grigg, 1997;Tsau and Heller, 1992;Wellington and Vinegar, 1985). (Bernard et al, 1980;Casteel and Djabbarah, 1988;Chang and Grigg, 1999;Dixit et al, 1994;Enick and Olsen, 2012;Heller, 1994;Holm and Garrison, 1988;Kahlil and Asghari, 2006;Moradi-Araghi et al, 1997;Preditis and Paulett, 1992;Syahputra et al, 2000;Tsau and Heller, 1992;Tsau and Grigg, 1997;Wang, 1984;Yaghoobi and Heller, 1994;Yin et al, 2009). Heller (1984) suggested in an early surfactant screening study that the most promising surfactant for CO 2 -foams appeared to be commercial anionic sulfonate surfactants.…”
Section: Type Of Surfactant Against Different Gas Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Bian et al, 2012;Chabert et al, 2014;Chang and Grigg, 1999;Dong, 2001; Kuehne et al, 1992;Moradi-Araghi et al, 1997;Mukherjee et al, 2014;Tsau and Grigg, 1997;Tsau and Heller, 1992;Wellington and Vinegar, 1985). (Bernard et al, 1980;Casteel and Djabbarah, 1988;Chang and Grigg, 1999;Dixit et al, 1994;Enick and Olsen, 2012;Heller, 1994;Holm and Garrison, 1988;Kahlil and Asghari, 2006;Moradi-Araghi et al, 1997;Preditis and Paulett, 1992;Syahputra et al, 2000;Tsau and Heller, 1992;Tsau and Grigg, 1997;Wang, 1984;Yaghoobi and Heller, 1994;Yin et al, 2009). Heller (1984) suggested in an early surfactant screening study that the most promising surfactant for CO 2 -foams appeared to be commercial anionic sulfonate surfactants.…”
Section: Type Of Surfactant Against Different Gas Componentsmentioning
confidence: 99%
“…Some authors observed a significant dependence on oil saturation on foam strength (Jensen and Friedmann, 1987;Schramm, 1994b;Mannhardt and Svorstøl, 1999;Yin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that foam has more stability in the presence of water flood residual oil, and foam injection reduces water flood, CO 2 flood, and water‐alternating‐gas flood residual oil by improving oil displacement efficiency . Formation of oil bank in the first few injected pore volumes, as results of gas mobility reduction and increased capillary number, leads to oil production by foam .…”
Section: Introductionmentioning
confidence: 99%
“…As an EOR application, foamy oil has been applied successfully in both of laboratory test (Maini, 1996;Bernard et al, 1980;Yin et al, 2009, Yan et al, 2006Kovscek et al, 1995) [4][5][6][7][8] and field studies (Blaker et al, 2002;Stevens and Martin, 1995) [9][10]. It was reported that the primary production of heavy oil from several reservoirs in western Canada is in the form of foamy oil.…”
Section: Introductionmentioning
confidence: 99%